Sustained participation in community-based physical activity by adolescents with cerebral palsy: a qualitative study. Issue 25 (4th December 2019) - Morris, Andrea; Imms, Christine; Kerr, Claire; Adair, Brooke
Abstract: Purpose: Short-term physical activity programs may encourage adolescents with cerebral palsy to participate in physical activity but how to sustain their involvement is not well known. This qualitative study aimed to identify facilitators that successfully sustain physical activity participation by adolescents with cerebral palsy. Materials and methods: Adolescents (12–18 years) with cerebral palsy [Gross Motor Function Classification System (GMFCS) levels I–V, without moderate-severe intellectual disability] who participated in regular physical activity were eligible, as well as one parent and an individual who facilitated their physical activity. Data were gathered using semi-structured interviews; verbatim transcripts were analysed using inductive thematic analysis within individuals ( n  = 15), triads ( n  = 5), and across participant groups (adolescents, parents and facilitators). Results: Five triads participated (male adolescents, 13–16 years, GMFCS levels I–III). Seven themes emerged: getting started, wanting to succeed, a sense of belonging, the coach is important, endorsement to continue, endorsement to support and being passionate. The themes were synthesized into the Framework for Sustained Participation, which describes the interaction among themes. Conclusions: The Framework for Sustained Participation highlights strategies that may be useful for adolescents, parents, sports facilitators, clinicians and researchers to help ambulatory male adolescents with cerebral palsy continue to participate in physical activity. Implications for rehabilitation: Sustaining participation in physical activity has the potential to enhance long-term health benefits of young people with cerebral palsy. Key facilitators of sustained physical activity in adolescents with cerebral palsy included tailoring the activity, getting the right coach and the adolescents' desire for health and fitness. The Framework of Sustained Participation may assist clinicians and facilitators who work with young people with cerebral palsy to structure their support in ways that will successfully sustain the adolescents' participation in physical activity.